A prospective study of risk factors and feto-maternal outcome of preterm labor in OG department of tertiary care centre of South Gujarat - Prajapati, Neha V.; Bhatia, Saral (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Every year globally, an estimated 15 million babies are born preterm and this number is rising over major parts of the world. Severe morbidity is common in neonates born before 32-34 weeks of gestation. Management of prematurity is a team approach by the obstetrician and the pediatrician. Methods: This prospective observational study was conducted in the Department of Obstetrics and Gynecology, NCH, Surat from October 2019 to October 2020. 120 consenting consecutive subjects fulfilling inclusion criteria were enrolled. Results: The most common risk factor for preterm labor in my study was PPROM (premature rupture of membranes). 27% subjects were diagnosed with threatened preterm labor. 22% subjects delivered preterm due to advanced labor. Labor arrest with tocolytic drug nifedipine was attempted in 30 subjects without any complications, which was successful in 19 subjects. The most common maternal complication in preterm labor was postpartum hemorrhage. All neonates were admitted to NICU, amongst them 45 developed complications. The most common complication in preterm neonates was respiratory distress. The rate of early neonatal death was 6.6%. Conclusions: Inspite of advances in antenatal care and neonatal services, preterm birth remains a burden to families. Strengthening of referral systems to make sure that high risk patients are managed at tertiary care centers with NICU facilities will improve the neonatal outcome.